Freestanding polypyrrole/carbon nanotube electrodes with high mass loading for robust flexible supercapacitors. (28th October 2020) - Wang, Songjie; Liang, Yongyin; Zhuo, Wenchen; Lei, Hang; Javed, Muhammad Sufyan; Liu, Botian; Wang, Zilong; Mai, Wenjie
Abstract : To meet the increasing requirement of flexible energy storage devices, it is critical to develop an electrode with commercial-level mass loading of active material for supercapacitors. Abstract : To meet the increasing requirement of flexible energy storage devices, it is critical to develop an electrode with commercial-level mass loading of active material for supercapacitors. Herein, we fabricated a high mass loading and freestanding CNT@PPy electrode (6.07 mg cm −2 ) by a simple vacuum filtration and low-temperature polymerization method. Moreover, owing to the high conductivity of CNT fiber networks offering a fast electron transporting passage, the optimized CNT@PPy electrode exhibits a prominent areal capacitance (2.6 F cm −2 ) with significantly improved mechanical properties (its ultimate tensile strength is 20.7 MPa, 23 times higher than that of pure CNT film). The freestanding all-solid-state symmetric supercapacitor based on the optimized CNT@PPy electrode obtains a high power density of 0.64 mW cm −2 at an energy density of 76.7 μW h cm −2 .